Value flow in music content production: a case study - Xuejie, Huang; Mei, Foong Ang (Human Resource Management Academic Research Society, 2022)
While the music industry significantly values music content production, it has also triggered disputes regarding copyrights and the attribution of interests within the same context. The value flow for the pre-digitalization and digitalization periods were compared before collecting typical work data from studio stakeholders involved in the content production of an original song. In this case study, the developing value flow was established from the perspectives of the content production team, which satisfied the scarcity of the commercial music production model. The findings indicated that individuals in the digital music industry value chain (MIVC) receive a bidirectional value flow, which represents its sustainability. The closed loop in the music business has been speculated to be the potential reason for internal frictions, which manifest as copyright conflict. The discussion proposes solutions for a healthier market, which may contribute to the higher quality production of musicians.